2015
DOI: 10.1111/1440-1681.12357
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of anaemia and inflammatory markers in chronic obstructive pulmonary disease

Abstract: SUMMARYThis systematic review synthesizes the relevant published articles on the prevalence of anaemia in patients with chronic obstructive pulmonary disease (COPD) and its relationship with inflammatory markers. The upregulation of erythropoietin in anaemia maintains homeostasis. However, anaemic COPD patients do not respond to increased levels of erythropoietin. The increased levels could be an indicator of the peripheral erythropoietin resistance in COPD. Anaemia and inflammation are associated with an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…(16). It has been suggested that oxygen supply to tissues was probably adversely affected when COPD was accompanied by increased systemic inflammation (17), and that erythropoietin resistance had also increased (18). This is supported by the significant relationship between the RDW/Hb ratio and mortality in our study.…”
Section: Discussionsupporting
confidence: 82%
“…(16). It has been suggested that oxygen supply to tissues was probably adversely affected when COPD was accompanied by increased systemic inflammation (17), and that erythropoietin resistance had also increased (18). This is supported by the significant relationship between the RDW/Hb ratio and mortality in our study.…”
Section: Discussionsupporting
confidence: 82%
“…"Spillover" of such local inflammatory process has been hypothesized as the cause of various systemic inflammatory changes and comorbidities including osteoporosis. [ 2 67 68 69 ] Increased production of such cytokines, indeed, has been demonstrated, and some of them are considered as therapeutic targets of COPD. [ 69 70 71 ] Moreover, systemic inflammation reflected by elevated C-reactive protein (CRP) in the general population has been linked to osteoporosis and to an increased bone resorption.…”
Section: Disease-specific Risk Factors For Osteoporosis In Copdmentioning
confidence: 99%
“…Historically, especially before the introduction of domiciliary oxygen, secondary polycythemia was a striking feature in COPD, but today the prevalence seems to be low 11. Instead, anemia might be more common, with a reported prevalence of 6.2%–46.3% 12,13…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, anemia might reflect iron deficiency, which has been linked to the development of pulmonary arterial hypertension14 and presence of chronic inflammation, which is associated with frailty 15. Concentrations of hemoglobin and hematocrit have been shown to provide prognostic information in different populations of COPD patients,1625 but in many of these studies patients with diseases associated with chronic anemia were excluded 12. While this strategy provides estimates of the prevalence and prognostic importance of hemoglobin directly ascribable to COPD, it does not reflect the importance of hemoglobin in a real-life COPD population, where most patients have numerous chronic diseases 5.…”
Section: Introductionmentioning
confidence: 99%